2010
DOI: 10.1016/j.elspec.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the cuprate high energy anomaly observed in ARPES

Abstract: Recently, angle-resolved photoemission spectroscopy has been used to highlight an anomalously large band renormalization at high binding energies in cuprate superconductors: the high energy "waterfall" or high energy anomaly (HEA). The anomaly is present for both hole-and electron-doped cuprates as well as the half-filled parent insulators with different energy scales arising on either side of the phase diagram. While photoemission matrix elements clearly play a role in changing the aesthetic appearance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…On the whole, the evolution of the QPB qualitatively agrees with the results of ARPES experiments on hole-doped compounds, [37][38][39][40][41] including the evolution of spectral intensity and changes in momentum space position and robustness of this "waterfall"-like appearance as a function of momentum as found in previous work on the single-particle bandstructure. 22,35,[42][43][44][45][46] Figure 3 shows the spectral function for an electrondoped system with model parameters t ′ = −0.3t, µ = 2.0t, and β = 3.0/t near optimal electron-doping (∼ 15%). The LHB, centered at ∼ −6 t, has been reduced in intensity from spectral weight transfer into the QPB which now disperses down across the Fermi level from the precursor in the UHB.…”
Section: B Resultsmentioning
confidence: 99%
“…On the whole, the evolution of the QPB qualitatively agrees with the results of ARPES experiments on hole-doped compounds, [37][38][39][40][41] including the evolution of spectral intensity and changes in momentum space position and robustness of this "waterfall"-like appearance as a function of momentum as found in previous work on the single-particle bandstructure. 22,35,[42][43][44][45][46] Figure 3 shows the spectral function for an electrondoped system with model parameters t ′ = −0.3t, µ = 2.0t, and β = 3.0/t near optimal electron-doping (∼ 15%). The LHB, centered at ∼ −6 t, has been reduced in intensity from spectral weight transfer into the QPB which now disperses down across the Fermi level from the precursor in the UHB.…”
Section: B Resultsmentioning
confidence: 99%
“…4, none of the data display both features simultaneously, potentially due to their weak intensity. From QMC simulations, 18,30 we believe that the latter, dispersionless feature is actually a remnant of the QPB and its faintness likely stems from matrix element effects. 18,23 The dichotomy in energy scales originates from the presence of the charge-transfer gap -or Mott gap in the case of the single-band Hubbard QMC simulations done here -located on the unoccupied or occupied side of the Fermi level.…”
Section: -40mentioning
confidence: 99%
“…Previous quantum Monte Carlo (QMC) work concentrating on band structure differences throughout the BZ for optimal, or near optimal, h-and e-doping, 18,30 and other work based on a cluster extension of dynamical mean field theory (DMFT) concentrating on momentum and doping dependence 31 indicated that the key features of the HEA can be captured by the strongly correlated, single-band Hubbard model through a substantial renormalization of the underlying bandsturcture due to strong electron-electron correlations that give rise to a coherent, shallow quasiparticle band (QPB) at low binding energy in these systems. The relevant Mott-Hubbard physics captured by this model already is believed to be substantially universal in the HTSCs providing an effective low energy theory.…”
mentioning
confidence: 99%
“…This difference was interpreted in terms of a shift of the chemical potential [14]. The experimental studies were accompanied by numerous theoretical papers [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].For the phenomenon of the HEA, a number of explanations have been suggested including Mott-Hubbard models with a transition from the coherent quasi-particle dispersion to the incoherent lower Hubbard band [5,18,21,26,32], a disintegration of the low-energy branch into a holon and spinon band due to a spin charge separation [2], a coupling to spin fluctuations [9,17,19,29,33], a coupling to phonons [7], string excitations of spinpolarons [32], a bifurcation of the quasi-particle band due to an excitation of a bosonic mode of charge 2e [22], and a coupling to plasmons [16]. These are all intrinsic interpretations in terms of many-body interactions leading to a change of the spectral function.…”
mentioning
confidence: 99%
“…This difference was interpreted in terms of a shift of the chemical potential [14]. The experimental studies were accompanied by numerous theoretical papers [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%